Pemberian Informasi Tentang Pemeriksaan Payudara Sendiri (Sadari) Pada Remaja - Masruroh, Masruroh; Cahyaningrum, Cahyaningrum; Hirawati, Heni; Purbowati, Purbowati (INDONESIAN JOURNAL OF COMMUNITY EMPOWERMENT (IJCE), 2021)
Detection of cancer can be done with breast self-examination or known as BSE. Breast self-examination (BSE) is an easy examination that every woman can do and can be done on her own. This action is important because almost 85% of abnormalities in the breast are actually found for the first time by the patient through a proper breast self-examination. This community service activity aims to increase students' motivation to carry out breast self-examination. The activity of providing information about breast self-examination was carried out at SMK Harapan Mulya Brangsong. The number of students who participated in the activity was 40 students. The results of the pretest showed that most of the students had less knowledge about breast self-examination as much as 25%. The results of the posttest showed that most of the students had knowledge in the good category of 45%. Socialization of the practice of breast self-examination is very important, so it is necessary to conduct health education about breast self-examination. Suggestions to the Harapan Mulya Vocational School to cooperate with the health workers so that they can provide continuous health problem counseling to the students of Harapan Mulya Brangsong Vocational School.ABSTRAKDeteksi kanker dapat dilakukan dengan pemeriksaan payudara sendiri atau yang dikenal dengan SADARI. Pemeriksaan payudara sendiri (SADARI) adalah pemeriksaan yang mudah yang bisa dilakukan setiap wanita dan bisa dilakukan sendiri. Tindakan ini penting karena hampir 85% kelainan di payudara justru ditemukan pertama kali oleh penderita melalui pemeriksaan payudara sendiri dengan benar. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan motivasi para siswa untuk melakukan pemeriksaan payudara sendiri ( SADARI) tiap bulannya.. Kegiatan pemberian informasi tentang pemeriksaan payudara sendiri dilaksanakan di SMK Harapan Mulya Brangsong. Jumlah siswa yang mengikuti kegiatan sebanyak 40 siswa. Hasil prestest didapatkan sebagian besar siswi mempunyai pengetahuan kurang tentang pemeriksaan payudara sendiri sebanyak 25%. Hasil posttest didapatkan sebagian besar siswi mempunyai pengetahuan dalam kategori baik sebesar 45%.Sosialisasi praktik pemeriksaan payudara sendiri dan sangatlah penting, sehingga perlu dilakukan pendidikan kesehatan tentang pemeriksaan payudara sendiri . Saran kepada Pihak SMK Harapan Mulya supaya bekerjasama keapada pihak tenaga kesehatan supaya dapat memberikan penyuluhan masalah kesehatan secara kontinyu kepada para siswa siswa SMK Harapan Mulya Brangsong.